Measuring employee readiness for knowledge management using intention to be involved with KM SECI processes - Nor Shahriza , Abdul Karim; Mohamed Razi, Mohamed Jalaldeen; Norshidah, Mohamed (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this study is to investigate the concept of knowledge management (KM) readiness using intention to be involved in the KM processes concept. These processes comprised of socialisation, externalisation, combination, and internalisation (SECI processes). The research also attempts to measure and validate the concept using data collected from the Sri Lankan telecommunication industry. Design/methodology/approach – Based on the established KM SECI process measures adopted and adapted, instruments were administered using a survey research methodology approach on 313 executives working in the selected organizations in the Sri Lankan telecommunication industry. A confirmatory factor analysis technique was performed to verify and validate the measurement model of the intention to be involved in KM processes model. Based on the revised measurement model, the level of intention to be involved in the KM SECI processes within the industry was then reported. Findings – The research finding provides the revised measurement model for employees’ intention to be involved in KM SECI processes. All four variables of the intention to be involved in KM SECI processes emerged as significant and reliable measures for KM readiness. The finding also indicates the positive level of intention among the employees in the Sri Lankan telecommunication industry to be involved in KM processes. Originality/value – The research provides a unique perspective of KM readiness, which is not much covered in the KM literature. The measurement produced can be used as a research tool for more exploratory and explanatory research in KM and, as an evaluative tool for employee readiness in ensuring the success of KM initiatives in organizations. The confirmed and validated set of measurement items can be used to measure the extent to which employees are ready to be involved with KM processes. Through the validated tool, more research can be conducted to explore the antecedents of such readiness perception.